Electrolytic capacitor and its manufacturing method
A two-layer solid electrolyte structure with a non-self-doped and self-doped conductive polymer combination addresses the issue of polymer deterioration in electrolytic capacitors, enhancing heat resistance and maintaining capacitance by reducing air permeation and oxygen contact.
Patent Information
- Application Number
- JP2020568118
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-25
- Filing Date
- 2020-01-17
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-01-17
AI Technical Summary
The deterioration of conductive polymers in solid electrolyte layers of electrolytic capacitors due to exposure to air, particularly in high-temperature environments, leads to increased equivalent series resistance (ESR) and decreased capacitance.
A two-layer solid electrolyte structure is implemented, comprising a first layer of non-self-doped conductive polymer and a second layer of self-doped conductive polymer, which fills voids in the first layer, reducing air permeation and contact with oxygen, thereby enhancing heat resistance.
The two-layer structure effectively suppresses the increase in ESR and decrease in capacitance of electrolytic capacitors even under high-temperature conditions, improving their performance and reliability.
Smart Images

Figure 0007607231000002 
Figure 0007607231000003 
Figure 0007607231000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor having a solid electrolyte layer and a method for manufacturing the same. [Background technology]
[0002] The electrolytic capacitor includes a capacitor element having a solid electrolyte layer, electrode terminals electrically connected to the capacitor element, and an exterior body that seals the capacitor element. The capacitor element includes, for example, an anode body, a dielectric layer formed on the anode body, and a solid electrolyte layer formed on the dielectric layer.
[0003] The solid electrolyte layer contains a conductive polymer. Patent Document 1 proposes a solid electrolytic capacitor including a dielectric oxide film formed on the surface of an anode body having pores, and a conductive polymer layer formed inside the pores and containing amines and a water-soluble self-doped conductive polymer having a sulfonic acid group. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2013-081099 Summary of the Invention
[0005] In electrolytic capacitors, the dielectric layer is usually formed to cover the surface of the porous portion formed in the anode body. The anode body is connected to an electrode terminal, and external air may enter the inside of the capacitor element through the porous portion of the anode body. When oxygen in the air comes into contact with the solid electrolyte layer, the conductive polymer contained in the solid electrolyte layer deteriorates, causing the electrolytic capacitor's ESR (equivalent series resistance) to increase and the capacitance to decrease.
[0006] One aspect of the present invention is a semiconductor device comprising an anode body, a dielectric layer formed on the anode body, and a dielectric layer formed on the dielectric layer. electric a solid electrolyte layer formed on the electrolyte layer, The solid electrolyte layer relates to an electrolytic capacitor including a first layer including a first conductive polymer and a second layer formed on the first layer and including a second self-doped conductive polymer.
[0007] Another aspect of the present invention is a method for manufacturing an anode body having a dielectric layer formed thereon, comprising: forming a solid electrolyte layer on the dielectric layer; The step of forming the solid electrolyte layer includes: A precursor of a first conductive polymer is deposited on the dielectric layer. Weight combining the first conductive polymer to form a first layer including the first conductive polymer; and forming a second layer containing the second conductive polymer on the first layer by applying a liquid composition containing a self-doping second conductive polymer to the first layer.
[0008] According to the present invention, Even after exposure to high temperatures, the increase in ESR of an electrolytic capacitor having a solid electrolyte layer can be suppressed, and the decrease in capacitance can be suppressed. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view illustrating an electrolytic capacitor according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an enlarged region II of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The electrolytic capacitor includes an anode body, a dielectric layer formed on the anode body, and a solid electrolyte layer formed on the dielectric layer. The anode body forms the dielectric layer and the solid electrolyte layer. surface of Surface area Large ToTo prevent this, the anode body usually has a porous portion on the surface. The porous portion contains many voids. One end of the anode body is connected to an electrode terminal, and air can enter the capacitor element from the electrode terminal side through the voids in the porous portion, causing deterioration of the conductive polymer contained in the solid electrolyte layer. Such deterioration of the conductive polymer is particularly noticeable in high-temperature environments.
[0011] According to an electrolytic capacitor according to one aspect of the present invention, a solid electrolyte layer is formed including a first layer including a first conductive polymer and a second layer formed on the first layer and including a second conductive polymer that is self-doped. As a second conductive polymer Self-doped Guidance By using a conductive polymer, it is easy to add a second conductive polymer to the first layer. Let in This is a self-doping type Guidance The conductive polymer is a non-self-doped conductive polymer. of This is because the particle diameter is stably maintained in the liquid composition in a small state compared to the case where the first layer has voids. Even if the first layer has voids, the voids in the first layer are filled with the second conductive polymer, so that even if air enters the capacitor element, it is difficult for it to penetrate through the solid electrolyte layer. Since the contact between the solid electrolyte layer and oxygen contained in the air can be reduced, deterioration of the conductive polymer is suppressed. This improves the heat resistance of the solid electrolyte layer and improves the heat resistance of the electrolytic capacitor. Therefore, it is possible to suppress an increase in the ESR (equivalent series resistance) of the electrolytic capacitor after the heat resistance test. It is also possible to suppress a decrease in the electrolytic capacitance of the electrolytic capacitor after the heat resistance test.
[0012] The self-doping conductive polymer refers to a conductive polymer having an anionic group that is directly or indirectly bonded to the backbone of the conductive polymer by a covalent bond. The anionic group of the conductive polymer itself functions as a dopant of the conductive polymer, so it is called a self-doping type. The anionic group includes, for example, an acidic group (acid type) or its conjugated anionic group (salt type).
[0013] The electrolytic capacitor and the method for manufacturing the same according to the above aspects of the present invention will be described more specifically below, with reference to the drawings as necessary. [Electrolytic capacitor] (Anode body) The anode body may contain a valve metal, an alloy containing a valve metal, a compound containing a valve metal, and the like. These materials may be used alone or in combination of two or more. For example, aluminum, tantalum, niobium, and titanium are preferably used as the valve metal. The anode body usually has a porous portion on the surface. Such an anode body is obtained, for example, by roughening the surface of a base material (foil-shaped or plate-shaped base material, etc.) containing a valve metal by etching or the like. The anode body may also be a molded body of particles containing a valve metal or a sintered body thereof. Since the sintered body has a porous structure, the entire anode body can be a porous portion.
[0014] (Dielectric layer) The dielectric layer is formed by anodizing the valve metal on the surface of the anode body by chemical conversion treatment or the like. The dielectric layer may be formed so as to cover at least a part of the anode body. The dielectric layer is usually formed on the surface of the anode body. Since the dielectric layer is formed on the surface of the porous part of the anode body, it is formed along the inner wall surfaces of the holes and depressions (pits) on the surface of the anode body.
[0015] The dielectric layer includes an oxide of a valve metal. For example, when tantalum is used as the valve metal, When aluminum is used as the valve metal, the dielectric layer contains Ta2O5, and when aluminum is used as the valve metal, the dielectric layer contains Al2O3. Note that the dielectric layer is not limited to these, and may be any layer that functions as a dielectric.
[0016] (solid electrolyte layer) The solid electrolyte layer is formed so as to cover the dielectric layer. The solid electrolyte layer does not necessarily have to cover the entire dielectric layer (entire surface), but may be formed so as to cover at least a part of the dielectric layer. The solid electrolyte layer includes a first layer containing a first conductive polymer, and a second layer containing a self-doping second conductive polymer formed on the first layer. When there is a region on the dielectric layer where the first layer is not formed, the second layer may be formed on the dielectric layer in this region.
[0017] (1st layer) The first conductive polymer may be, for example, a non-self-doping conductive polymer. When the first layer contains a non-self-doping conductive polymer, voids are likely to occur in the first layer. Even in such a case, however, by forming a second layer of a self-doping second conductive polymer on the first layer, the second conductive polymer can be prevented from being mixed with the first layer. Get in Therefore, the heat resistance of the solid electrolyte layer can be improved. In addition, examples of non-self-doping conductive polymers include conductive polymers that do not have anionic groups (specifically, sulfonic acid groups, carboxyl groups, phosphoric acid groups, phosphonic acid groups, and salts thereof) directly or indirectly bonded to the backbone of the conductive polymer by covalent bonds.
[0018] As the non-self-doping conductive polymer, polypyrrole, polythiophene, polyaniline, etc. are preferable. These may be used alone, or two or more may be used in combination, or a copolymer of two or more monomers may be used. In this specification, polypyrrole, polythiophene, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyaniline, etc. as a basic skeleton, respectively. Therefore, polypyrrole, polythiophene, polyaniline, etc. may also include their respective derivatives (substitutes having a substituent other than anionic groups, etc.). For example, polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT), etc. Among these, polypyrroles (polypyrrole and its derivatives) may cause voids in the first layer. Even when the first layer contains such polypyrroles, in order to form a second layer containing a second conductive polymer on the first layer, the second conductive polymer may be formed. but On the first layer Get in This makes it possible to ensure high heat resistance of the solid electrolyte layer.
[0019] The weight average molecular weight of the first conductive polymer is not particularly limited, but is, for example, not less than 1,000 and not more than 1,000,000. In this specification, the weight average molecular weight is a weight average molecular weight measured by gel permeation chromatography (GPC) using polystyrene as a standard.
[0020] The first layer may include a self-doping second conductive polymer. The second conductive polymer may be added to the first layer when the first layer is formed, or may be added to the first layer when the second layer is formed. Let in The first layer may be doped with the dopant. Guidance Examples of the conductive polymer include those described below.
[0021] The first layer may be a single layer or may be composed of multiple layers. When the first layer is composed of multiple layers, the first conductive polymer contained in each layer may be the same or different.
[0022] The first layer may further include a dopant. The dopant may be, for example, an aniline. Anions and / or polyanions are used.
[0023] Examples of the anion include, but are not limited to, sulfate ions, nitrate ions, phosphate ions, borate ions, and organic sulfonate ions. Examples of the dopant that generates sulfonate ions include paratoluenesulfonic acid and / or naphthalenesulfonic acid. The anion may be contained in the first layer in the form of a salt.
[0024] Examples of polyanions include, but are not limited to, polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacrylsulfonic acid, and / or polymethacrylsulfonic acid. The polyanion may be contained in the first layer in the form of a salt. In the first layer, the anion and / or the polyanion may form a conductive polymer complex together with the first conductive polymer.
[0025] As described above, the dielectric layer is formed along the inner wall surfaces of the holes and pits in the porous portion of the anode body, so the first layer formed on the dielectric layer is also formed in the porous portion of the anode body. The distribution state of the first layer in the porous portion is not particularly limited, but the first layer may be formed over the entire porous portion, or the distribution state of the first layer may differ between the surface layer and the inside of the porous portion. For example, the first layer may be more concentrated in the inside than in the vicinity of the surface layer of the porous portion. The amount The porous portion may have a small number of layers. Also, a second layer may be formed on the first layer formed in the porous portion. The second layer may be formed (or exist) in the voids of the porous portion. In such a case, air is less likely to pass through the porous portion, which enhances the effect of suppressing deterioration of the solid electrolyte layer and further suppresses the increase in ESR. Also, the effect of suppressing the decrease in capacitance can be further enhanced.
[0026] The first layer can be formed, for example, by chemical polymerization and / or electrolytic polymerization of a precursor (such as a raw material monomer) of the first conductive polymer. Alternatively, the first layer can be formed by contacting a liquid composition (first liquid composition) containing at least the first conductive polymer with the dielectric layer. In particular, electrolytic polymerization is likely to proceed on the surface side (surface side of the porous portion) of the first layer, so that the first layer is likely to be formed densely, but it is difficult to proceed inside, so that voids are likely to occur. Air is likely to enter the capacitor element through these voids, which is likely to cause deterioration of the solid electrolyte layer. However, even if the first layer is an electrolytic polymerization film that is likely to cause voids in this way, by forming the second layer, the permeation of air can be reduced and deterioration of the solid electrolyte layer can be suppressed. Therefore, particularly when the first layer is formed by electrolytic polymerization, it is preferable to form the second layer (more specifically, to form the second conductive polymer into the first layer). Let in ) is a significant effect. When the second layer is formed on the electrolytically polymerized film as the first layer, the amount of the first layer is smaller in the interior of the porous portion than in the vicinity of the surface layer, as described above. The second layer is also formed on the first layer formed in the porous portion, and the second layer is formed in a state in which it penetrates into or fills the voids in the porous portion (or the first layer).
[0027] (2nd layer) Examples of the anionic group of the second conductive polymer include a sulfonic acid group, a carboxyl group, a phosphoric acid group, a phosphonic acid group, or a salt thereof (such as a salt with an inorganic base or a salt with an organic base). The second conductive polymer may have one type of anionic group, or may have two or more types of anionic groups. The anionic group is preferably a sulfonic acid group or a salt thereof, or may be a combination of a sulfonic acid group or a salt thereof and an anionic group other than a sulfonic acid group or a salt thereof. The amount of anionic groups contained in the second conductive polymer is preferably 1 to 3, and more preferably 1 or 2 (particularly 1), per molecule corresponding to the main skeleton of the second conductive polymer.
[0028] The second conductive polymer may be polypyrrole having an anionic group, Polythiophene having an anionic group, polyaniline having an anionic group, etc. are preferred. These may be used alone or in combination of two or more, and the second conductive polymer may be a copolymer of two or more monomers. Polypyrrole, polythiophene, polyaniline, etc. may also include their respective derivatives (such as a substitute having an anionic group and a substituent other than the anionic group). Among these, for example, self-doped PEDOTs (such as PEDOT and its derivatives) are preferred from the viewpoint of further enhancing the effect of suppressing the increase in ESR and the decrease in capacitance even after exposure to a high-temperature environment.
[0029] On the first layer Let them in From the viewpoint of ease of preparation, the weight average molecular weight of the second conductive polymer is preferably 100,000 or less, and more preferably 30,000 or less. The weight average molecular weight of the second conductive polymer is, for example, 1,000 or more. Furthermore, the viscosity of the second liquid composition containing the second conductive polymer is not particularly limited as long as it is 500 mPa·s or less at 25°C and 60 rpm when evaluated with a Brookfield viscometer, but is preferably 300 mPa·s or less, and more preferably 100 mPa·s or less.
[0030] The second layer may contain a conductive polymer other than the second conductive polymer (e.g., a non-self-doping conductive polymer, etc.), but preferably contains a large amount of the second conductive polymer. The ratio of the second conductive polymer to the total conductive polymer contained in the second layer is, for example, 90 mass % or more, and may be 100 mass %.
[0031] The second conductive polymer has an anionic group, and the second layer may contain a dopant as necessary. For example, an anion and / or a polyanion is used as the dopant. In the second layer, the anion and / or the polyanion may form a conductive polymer complex together with the conductive polymer. The anion and the polyanion may be selected from those described for the first layer.
[0032] The content of the dopant in the second layer is, for example, 0 to 50 parts by mass, and preferably 0 to 10 parts by mass or 0.1 to 10 parts by mass, relative to 100 parts by mass of the second conductive polymer.
[0033] The second layer may be a single layer or may be composed of multiple layers. When the second layer is composed of multiple layers, the second conductive polymer contained in each layer may be the same or different.
[0034] The second layer may further contain an alkali, if necessary. The alkali can be selected from those exemplified for the first layer.
[0035] The solid electrolyte layer may further contain other components within the range not impairing the effects of the present invention.
[0036] FIG. 1 is a cross-sectional view that shows a schematic structure of an electrolytic capacitor according to an embodiment of the present invention. FIG. 2 is an enlarged cross-sectional view that shows a schematic view of region II in FIG. 1. The electrolytic capacitor 1 includes a capacitor element 2, a resin sealing material (exterior body) 3 that seals the capacitor element 2, and an anode terminal 4 and a cathode terminal 5, at least a part of which is exposed to the outside of the resin sealing material 3. The anode terminal 4 and the cathode terminal 5 can be made of, for example, a metal (copper or a copper alloy, etc.). The resin sealing material 3 has an outer shape of a substantially rectangular parallelepiped, and the electrolytic capacitor 1 also has an outer shape of a substantially rectangular parallelepiped. For example, an epoxy resin can be used as the material for the resin sealing material 3.
[0037] Capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. Cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7, and a cathode extraction layer 10 covering the solid electrolyte layer 9. Cathode extraction layer 10 has, for example, a carbon layer 11 and a silver paste layer 12.
[0038] The anode body 6 has a porous portion 6a, and includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. In the region of the anode body 6 not facing the cathode portion 8, an insulating separation layer 13 is formed in a strip-like shape covering the surface of the anode body 6 in a portion adjacent to the cathode portion 8, and contact between the cathode portion 8 and the anode body 6 is restricted. Another part of the region of the anode body 6 not facing the cathode portion 8 is electrically connected to the anode terminal 4 by welding. The cathode terminal 5 is electrically connected to the cathode portion 8 via an adhesive layer 14 formed of a conductive adhesive.
[0039] Principal surfaces 4S and 5S of anode terminal 4 and cathode terminal 5 are exposed from the same surface of resin sealing material 3. These exposed surfaces are used for soldering to a substrate (not shown) on which electrolytic capacitor 1 is to be mounted.
[0040] Carbon layer 11 may be made of any material as long as it is conductive, and may be made of, for example, a conductive carbon material (such as graphite). Silver paste layer 12 may be made of, for example, a composition containing silver powder and a binder resin (such as an epoxy resin). The configuration of cathode extraction layer 10 is not limited thereto, and may be any material as long as it has a current collecting function.
[0041] The solid electrolyte layer 9 is formed so as to cover the dielectric layer 7. The dielectric layer 7 is formed along the surface of the anode body 6 (the surface including the inner wall surfaces of the holes). The surface of the dielectric layer 7 has an uneven shape formed in accordance with the shape of the surface of the anode body 6. The solid electrolyte layer 9 is preferably formed so as to fill in such unevenness of the dielectric layer 7.
[0042] The solid electrolyte layer 9 comprises a first layer 9a formed on the dielectric layer 7 and a second layer 9b formed on the first layer. The first layer 9a contains a first conductive polymer, and the second layer 9b contains a self-doping second conductive polymer. The first layer 9a is formed (or filled) in the porous portion 6a of the anode body 6, and has voids P within the layer. The second conductive polymer is added to the first layer 9a when the second layer 9b is formed. It's getting in Therefore, the second conductive polymer is present in the voids P in the first layer 9a. Entry , In the gap P A second layer 9b is formed. Although the voids P are shown diagrammatically in the figure, at least a part of the voids P is continuous within the porous portion (or the first layer 9a).
[0043] The electrolytic capacitor according to the above aspect is not limited to the electrolytic capacitor having the above structure, and can be applied to electrolytic capacitors having various structures. Specifically, the present invention can be applied to a wound electrolytic capacitor, an electrolytic capacitor using a sintered body of metal powder as an anode body, and the like.
[0044] [Manufacturing method of electrolytic capacitors] The method for producing an electrolytic capacitor according to the above aspect includes a step of preparing an anode body having a dielectric layer formed thereon (first step), and a step of forming a solid electrolyte layer on the dielectric layer (second step). The method for producing an electrolytic capacitor may also include a step of preparing an anode body prior to the first step. The method may further include a step of forming a cathode extraction layer and / or a step of sealing the capacitor element. Each step will now be described in more detail.
[0045] (Step of preparing the anode body) In this step, the anode body is formed by a known method depending on the type of the anode body. The anode body can be prepared, for example, by roughening the surface of a foil- or plate-shaped substrate containing a valve metal. By roughening, a porous portion is formed in the surface layer of the anode body. The roughening can be performed by etching the substrate surface (for example, electrolytic etching) as long as the substrate surface can be provided with irregularities.
[0046] Also, a powder of a valve metal is prepared, and a bar-shaped anode terminal is placed in the powder at one end in the longitudinal direction. With the end embedded, a green body is formed into a desired shape (for example, a block shape) and this green body may be sintered to form an anode body having a porous structure in which one end of the anode terminal is embedded.
[0047] (1st step) In the first step, a dielectric layer is formed on the anode body. The dielectric layer is formed by anodizing the anode body. The anodization can be performed by a known method, for example, chemical conversion treatment. The chemical conversion treatment can be performed, for example, by immersing the anode body in a chemical conversion solution to impregnate the surface of the anode body with the chemical conversion solution, and applying a voltage between the anode body as an anode and a cathode immersed in the chemical conversion solution. As the chemical conversion solution, for example, an aqueous solution of phosphoric acid or the like is preferably used.
[0048] (2nd process) In the second step, the solid electrolyte layer is formed so as to cover at least a part of the dielectric layer. The second step includes, for example, a step of forming a first layer on the dielectric layer and a step of forming a second layer on the first layer.
[0049] (Step of forming the first layer) The first layer may be formed by contacting the dielectric layer with a first liquid composition containing a first conductive polymer, but is preferably formed by chemically polymerizing and / or electrolytically polymerizing a precursor of the first conductive polymer. In particular, when the first layer containing the first conductive polymer is formed by polymerizing a precursor by electrolytic polymerization, voids may be formed in the first layer, so it is preferable to form the first layer by applying a second conductive polymer to the first layer. Let in This makes it easy to obtain a remarkable effect. In the case of electrolytic polymerization, a conductive precoat layer may be formed prior to the electrolytic polymerization. The first layer may be formed directly on the dielectric layer, or may be formed via the precoat layer.
[0050] The first liquid composition containing the first conductive polymer may be, for example, a dispersion (or solution) of the first conductive polymer, or a dispersion (or solution) of a conductive polymer complex of the first conductive polymer and a dopant.
[0051] In the case of chemical polymerization, for example, the first layer is formed using a first liquid composition containing a precursor of the first conductive polymer, a dispersion medium (or solvent), an oxidizing agent, and, if necessary, a dopant. After the first liquid composition is applied to the dielectric layer, it may be heated.
[0052] In the case of electrolytic polymerization, for example, the first layer is formed using a first liquid composition containing a precursor of a first conductive polymer, a dispersion medium (or solvent), and, if necessary, a dopant. The first layer is formed, for example, by immersing an anode body on which a dielectric layer and a precoat layer are formed, in the first liquid composition, and supplying power from a supply electrode to the precoat layer as an electrode. The precoat layer is formed, for example, from a conductive material (conductive polymer, inorganic conductive material, etc.). The conductive material constituting the precoat layer is not particularly limited, and for example, a known material can be used.
[0053] The first conductive polymer and the dopant may be those exemplified above. The precursor of the first conductive polymer may be a monomer constituting the first conductive polymer, and / or an oligomer in which several monomers are linked together. The dispersion medium (or solvent) may be, for example, water, an organic solvent, or a mixture thereof. The organic solvent may be, for example, a monohydric alcohol (methanol, ethanol, propanol, etc.), a polyhydric alcohol (ethylene glycol, glycerin, etc.), or an aprotic polar solvent (N,N-dimethylformamide, dimethylsulfoxide, acetonitrile, acetone, benzonitrile, etc.). The first liquid composition may further contain an alkali and / or other components.
[0054] (Step of forming the second layer) The second layer is formed on the first layer, for example, by applying a second liquid composition containing a self-doping second conductive polymer to the first layer. The second layer can be formed, for example, by immersing an anode body having the first layer formed on a dielectric layer in the second liquid composition, or by applying or dropping the second liquid composition onto an anode body having the first layer formed on a dielectric layer, and then drying the composition.
[0055] The second liquid composition contains a second conductive polymer, a dispersion medium (or solvent), and, if necessary, a dopant. As the second conductive polymer and the dopant, those exemplified above can be used. As the dispersion medium (or solvent), those exemplified for the first liquid composition can be used. The second liquid composition may further contain an alkali and / or other components.
[0056] The second liquid composition may be, for example, a dispersion (or solution) of the second conductive polymer, or a dispersion (or solution) of a conductive polymer complex of the second conductive polymer and a dopant. The second liquid composition may be obtained, for example, by oxidatively polymerizing a precursor of the second conductive polymer in a dispersion medium (or solvent). Examples of this precursor include a monomer constituting the second conductive polymer, and / or an oligomer in which several monomers are linked together. The second liquid composition containing the conductive polymer complex may be obtained by oxidatively polymerizing a precursor of the second conductive polymer in a dispersion medium (or solvent) in the presence of a dopant.
[0057] The average particle size of the particles of the second conductive polymer (or conductive polymer complex) dispersed in the second liquid composition is, for example, 800 nm or less. Let them in From the viewpoint of ease of use, the average particle size is preferably 300 nm or less, more preferably 100 nm or less. The lower limit of the average particle size is not particularly limited, but is, for example, 5 nm or more. In this specification, the average particle size of the conductive polymer (or conductive polymer complex) can be determined, for example, from the particle size distribution by dynamic light scattering method.
[0058] (Step of forming cathode extraction layer) In this step, a cathode extraction layer is formed by sequentially laminating a carbon layer and a silver paste layer on the solid electrolyte layer formed in step 2. By forming the cathode extraction layer, a capacitor element can be obtained. A conductive adhesive layer is disposed on the surface of the cathode extraction layer, and one end of the cathode terminal is electrically connected to the capacitor element via this adhesive layer. As the cathode terminal, any electrode terminal used in electrolytic capacitors can be used without particular limitation, and for example, what is called a lead frame may be used.
[0059] (Process for sealing the capacitor element with resin sealing material) The formed capacitor element is sealed with a resin material together with, for example, a portion of each of the anode terminal 4 and the cathode terminal 5. This sealing forms the resin sealing material 3. The resin material is preferably a thermosetting resin (such as an epoxy resin) or a resin composition. The resin sealing material 3 contains a cured product of the thermosetting resin or the resin composition.
[0060] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0061] Example 1 An electrolytic capacitor 1 shown in FIG. 1 was fabricated in the following manner, and its characteristics were evaluated. (1) Anode body preparation process An aluminum foil (thickness: 100 μm) was prepared as a substrate, and the surface of the aluminum foil was subjected to an etching treatment to obtain an anode body 6.
[0062] (2) Step of forming dielectric layer 7 The anode body 6 is immersed in a phosphoric acid solution with a concentration of 0.3 mass % (liquid temperature 70°C) and a direct current voltage of 70 V is applied for 20 minutes, whereby a layer containing aluminum oxide (Al2O3) is formed on the surface of the anode body 6. Dielectric layer 7 was formed. After that, insulating resist tape (separation layer 13) was attached to predetermined locations of anode body 6.
[0063] (3) Step of forming the first layer An aqueous dispersion (first liquid composition) containing pyrrole and a dopant (naphthalenesulfonic acid) was prepared. The concentration of pyrrole in the first liquid composition was 2 mass %, and the concentration of the dopant was 10 mass %.
[0064] The anode body 6 on which the dielectric layer 7 was formed was immersed in a liquid composition containing a conductive material to form a precoat layer. The anode body 6 on which the dielectric layer 7 and the precoat layer were formed was immersed in a first liquid composition, and electrolytic polymerization of pyrrole was carried out using the precoat layer as an electrode to form a first layer containing polypyrrole as a first conductive polymer.
[0065] (4) Step of forming the second layer An aqueous dispersion (second liquid composition) containing a second conductive polymer was prepared. The concentration of the second conductive polymer in the second liquid composition was 4 mass%, and the average particle size of the second conductive polymer was 100 nm. As the second conductive polymer, PEDOT having a sulfonic acid group directly bonded to the PEDOT skeleton was used.
[0066] The anode body 6 on which the first layer 9a was formed was immersed in the second liquid composition and then dried at 120°C for 10 to 30 minutes to form the second layer 9b. At this time, the second liquid composition permeates the first layer 9a, and the second conductive polymer is also filled into the voids P formed in the first layer 9a, so that a second layer containing the second conductive polymer is formed in the voids P of the first layer. In this manner, a solid electrolyte layer 9 composed of the first layer 9a and the second layer 9b was formed.
[0067] (5) Step of forming a cathode extraction layer A dispersion liquid in which graphite particles are dispersed in water was applied to the surface of the solid electrolyte layer 9, and then dried to form the carbon layer 11.
[0068] Next, a silver paste containing silver particles and a binder resin (epoxy resin) was applied to the surface of carbon layer 11, and then heated to harden the binder resin, thereby forming silver paste layer 12. In this manner, cathode extraction layer 10 composed of carbon layer 11 and silver paste layer 12 was formed. In this manner, capacitor element 2 was obtained.
[0069] (6) Assembly of electrolytic capacitors An anode terminal 4, a cathode terminal 5, and an adhesive layer 14 were further arranged on the capacitor element 2, and the resulting structure was sealed with a resin sealing material 3 to produce an electrolytic capacitor.
[0070] Comparative Example 1 An electrolytic capacitor was produced in the same manner as in Example 1, except that the second layer was not formed.
[0071] Comparative Example 2 As the second liquid composition for forming the second layer, an aqueous dispersion of PEDOT doped with polystyrene sulfonate (PSS), a non-self-doping conductive polymer, was used. The concentration of the conductive polymer in the second liquid composition was 4 mass%, and the average particle diameter of the conductive polymer was 400 nm. Except for these, the electrolytic capacitor was produced in the same manner as in Example 1.
[0072] [evaluation] The electrolytic capacitors of the examples and comparative examples prepared above were evaluated for capacitance and ESR by the following procedure. In a 20℃ environment, using a 4-terminal LCR meter, Electrolytic capacitor Initial capacitance value C0 (μF) , and The initial ESR value X0 (mΩ) at a frequency of 100 kHz was measured. Next, the rated voltage was applied to the electrolytic capacitor for 125 hours at a temperature of 145°C (heat resistance test). After that, the capacitance value C1 (μF) and ESR Value X1( mΩ) were measured. Capacitance value C1 from Initial capacitance value C0 The value subtracted from Initial capacitance value C0 Divide by and multiply by 100 to get the capacitance Amount The rate of change was calculated. Moreover, the ESR change rate was calculated by subtracting the initial ESR value X0 from the ESR value X1, dividing the result by the initial ESR value X0, and multiplying the result by 100. When the rate of change in Comparative Example 1 is taken as 100, Example 1, Comparative Example 2 Ratio of the rate of change in (Relative value) was calculated and used as an index for evaluating capacitance and ESR. The results are shown in Table 1. Example 1 is A1, and Comparative Examples 1 and 2 are R1 and R2.
[0073] [Table 1]
[0074] Working Example 1 Now, a comparative example 1、2 The change rates of capacitance and ESR are smaller than those of the example. 1 So, the self-doping type second conductive polymer in First layer voids Filled with It is believed that this is because the contact of air with the solid electrolyte layer was suppressed, and the deterioration of the conductive polymer was suppressed, thereby improving the heat resistance of the electrolytic capacitor. In particular, in Comparative Example 2, which used a non-self-doping conductive polymer, the change rates of ESR and capacitance were large. This is believed to be because, in the liquid composition of Comparative Example 2, the particle diameter of the conductive polymer was large, and the permeability into the first layer was low. [Industrial Applicability]
[0075] In the electrolytic capacitor according to one aspect of the present invention, even when exposed to a high-temperature atmosphere, the deterioration of the conductive polymer contained in the solid electrolyte layer is suppressed, and the increase in ESR can be suppressed. In addition, the decrease in capacitance can be suppressed. Therefore, the electrolytic capacitor can be used in various applications where high heat resistance is required. [Explanation of symbols]
[0076] 1: electrolytic capacitor, 2: capacitor element, 3: resin sealing material, 4: anode terminal, 4S: main surface of anode terminal, 5: cathode terminal, 5S: main surface of cathode terminal, 6: anode body, 7: dielectric layer, 8: cathode part, 9: solid electrolyte layer, 9a: first layer, 9b: second layer, 10: cathode lead layer, 11: carbon layer, 12: silver paste layer, 13: separation layer, 14: adhesive layer
Claims
1. An electrochemical device comprising: an anode body having an uneven surface; a dielectric layer formed on the anode body and having an uneven surface shape corresponding to the surface shape of the anode body; and a solid electrolyte layer formed on the dielectric layer; the solid electrolyte layer includes a first layer containing a non-self-doping first conductive polymer and filling at least a part of the uneven shape on the surface of the dielectric layer, and a second layer formed on the first layer and containing a self-doping second conductive polymer; An electrolytic capacitor, wherein the first layer has voids in which the first conductive polymer is not present, and the second conductive polymer is present in the voids.
2. An electrolytic capacitor as described in claim 1, wherein the second layer does not contain the first conductive polymer.
3. An electrolytic capacitor as described in claim 1 or 2, further comprising a cathode extraction layer not containing a conductive polymer directly above the second layer.
4. 4. The electrolytic capacitor according to claim 1, wherein the second conductive polymer has a weight average molecular weight of 30,000 or less.
5. The electrolytic capacitor according to any one of claims 1 to 4, wherein the second conductive polymer is a self-doped poly(3,4-ethylenedioxythiophene) type.
6. 6. The electrolytic capacitor according to claim 1, wherein the first conductive polymer is a polypyrrole.
7. The first layer includes a film formed by polymerizing a precursor of the first conductive polymer, The electrolytic capacitor according to any one of claims 1 to 6, wherein the second layer comprises a film formed by applying a liquid composition containing the second conductive polymer to the first layer.
8. An electrolytic capacitor as described in claim 7, wherein the first layer includes a film formed by electrolytic polymerization of a precursor of the first conductive polymer.
9. A step of preparing an anode body having an uneven surface; forming a dielectric layer on the anode body, the dielectric layer having an uneven surface corresponding to a surface shape of the anode body; forming a solid electrolyte layer on the dielectric layer; The step of forming the solid electrolyte layer includes: a first step of polymerizing a precursor of a non-self-doping first conductive polymer to form a first layer containing the first conductive polymer and filling at least a part of the uneven shape on the surface of the dielectric layer; a second step of depositing a liquid composition containing a second self-doping conductive polymer on the first layer to form a second layer containing the second conductive polymer on the first layer; In the first step, voids in which the first conductive polymer is not present are generated in the first layer, In the second step, the second conductive polymer is allowed to penetrate into the gap.
10. A method for manufacturing an electrolytic capacitor as described in Claim 9, wherein the first step includes a step of electrolytically polymerizing a precursor of the first conductive polymer to form the first layer.
11. particles of the second conductive polymer are dispersed in the liquid composition; The method for producing an electrolytic capacitor according to claim 9 or 10, wherein the particles have an average particle size of 100 nm or less.
12. A method for manufacturing an electrolytic capacitor according to any one of claims 9 to 11, wherein the second conductive polymer is a self-doped poly(3,4-ethylenedioxythiophene) type.
13. A method for manufacturing an electrolytic capacitor according to any one of claims 9 to 12, wherein the first conductive polymer is a polypyrrole.
Citation Information
Patent Citations
Solid electrolytic capacitor and its manufacturing method
JP2005252213A
Method of manufacturing solid-state electrolytic capacitor
JP2007184318A
Solid electrolytic capacitor
JP2010153454A
Method of manufacturing solid electrolytic capacitor
JP2011192983A
Elastic surface wave device
JP2013081099A
